Surface functionalization of bioactive glasses and hydroxyapatite with polyphenols from organic red grape pomace. Issue 3 (26th May 2021) - Riccucci, Giacomo; Cazzola, Martina; Ferraris, Sara; Gobbo, Virginia Alessandra; Miola, Marta; Bosso, Antonella; Örlygsson, Gissur; Ng, Chuen How; Verné, Enrica; Spriano, Silvia
Abstract: An extract of polyphenols was obtained from organic red grape pomace, chemically analyzed, and used for functionalization of two bioactive glasses and porous hydroxyapatite. Functionalization is effective on hydroxyapatite and the bioactive glass with higher surface reactivity with a different grafting mechanism. Grafting does not inhibit redox and radical scavenging activity of polyphenols. The grafted polyphenols make a continuous layer with an almost complete surface coverage. Polyphenols are released with different kinetics according to the mechanism of grafting and maintain their redox activity. A homogeneous thin layer of polyphenols is still firmly grafted on both substrates after 28 days of soaking and it still maintains radical scavenging activity. The functionalized samples can be sterilized by gamma irradiation. Abstract : Functionalization of hydroxyapatite and bioactive glasses with natural polyphenols: Effect of the substrate on efficacy and mechanism of functionalization.